Igneous breccia system of the Shand porphyry Cu-Mo deposit, Northern Mongolia - Ganbat, Bayaraa; Odgerel, Dashdorjgochoo; Altankhuyag, Dorjyunden; Sanchir, Dorjgochoo; Altanzul, Chikalov; Azjargal, Gurdorj (Mongolian Geoscientist, 2022)
The Shand Cu-Mo deposit is located in the Orkhon-Selenge depression, Northern Mongolia. It lies near the Erdenetiin Ovoo porphyry Cu-Mo deposit, which together define one of Northern Mongolian’s most economically significant metallogenic belts. In the Shand Cu-Mo (Au?) deposit, several ore related breccia types are associated with the porphyritic granodiorite intrusions, and they contain pre-, synand post-mineralized porphyry stocks, magmatic-hydrothermal and intrusive breccia. There are genetically at least two type of hydrothermal breccias have recognized in Shand deposit, i.e. magmatic-hydrothermal breccia and intrusive breccia. Magmatichydrothermal breccia is presented spatially associated with intrusions but extending sub vertical which characterized by angular fragments/clasts supported or infilled by minerals commonly indicative of high temperature and salinity (e.g. tourmaline, feldspar), silicas, carbonates and sulphides (Cu, Mo, (Au)) matrix derived from hydrothermal fluids precipitation. May grade downwards into cupolas of intrusive with or without intrusive breccia and pegmatite where occur at approximately deep from 250-1300 m depth. Intrusive breccia is mostly occurred in contact between margin intrusions at shallow depth which is mainly composed by granodiorite porphyry, granodiorite and dacite. Our drillhole relogging and petrographical observations are granodiorite hosted breccia and granodiorite porphyry hosted breccia. Here, we present an integrated study involving detailed drillhole logging, and petrographical observations to elucidate the genetic relationship and evolution of the Shand deposit for magmatic-hydrothermal breccia and intrusive breccia. Also, we propose that the magmatic breccia types indicate emplacement of igneous rocks from initially dacitic magma composition.